Better together : creating community in an uncertain world - Tate, Nikki, 1962- (Victoria, British Columbia : Orca Book Publishers, 2018)
"Explore the different types of communities people create to meet their need for companionship."--
Includes bibliographical references and index.
Issued also in electronic formats.
Keywords: Communities -- Juvenile literature; Fellowship -- Juvenile literature; Social groups -- Juvenile literature; Social participation -- Juvenile literature